Teaching Literature in the Digital Age: Some Theoretical Reflections - Bennis, Mohammed (International Journal of Language and Literary Studies, 2024)
This paper attempts to address the challenges facing the teaching of literature in the digital age. I argue that the rise, normalization and ubiquity of new technology entail the rapid integration of technology in the teaching of literature to dovetail with the increasing expectations and aspirations of the new generation who have grown up with technology and have abundantly assimilated digital cultures. For them technology is much more than digital tools and devices that can be interpreted as semiotic signifiers of the digital age; it also epitomizes the new generation’s identities, mindsets, attitudes and cultural practices. Teachers are called upon to address the demands of the new generation and seriously reflect on propounding plausible and innovative pedagogical actions and strategies that would transform traditional methods which, I believe, seem cacophonous with the new generation of learners. Few would contest the fact that the traditional classroom with its classical methods of teaching is no longer compatible with the changing needs of the current generation of students who expect to be addressed as digitally cultivated learners for whom technology is a normative practice. It is incumbent on teachers to assimilate the fact that today’s students are globally advanced learners who are aware of the crucial role of technology in the learning process and would fail to cope with the traditional classroom and its limited resources. Another daunting challenge facing the teaching of literature lies in motivating the digital age students to read, analyse and interpret literary texts through the integration of technology and encouraging them to enjoy literature and sustain their interest. The new learners are more enticed by graphics and visual content than texts. I argue that converting literary texts to visual productions and platforms would help digitally literate students regain interest in the literary texts and be engaged in the analytical process.